2023
DOI: 10.1097/brs.0000000000004620
|View full text |Cite
|
Sign up to set email alerts
|

SRS-22r Self-Image After Surgery for Adolescent Idiopathic Scoliosis at 10 Year Follow-up

Abstract: Study Design. Retrospective cohort Objective. To examine SRS-Self Image scores at up to 10 years after surgery for adolescent idiopathic scoliosis (AIS). Summary of Background Data. Self-image is complex with implications for surgical and patient-reported outcomes after AIS surgery. Surgically modifiable factors that impact self-image are inconsistently reported in the literature with few longer-term reports. We examined the rate and durability of self-image improvement. Materials and Methods. An AIS reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Thus, gathering patient input in the surgical planning phase is critical to ensuring a favorable postoperative outcome ( 21 - 23 ). The SRS-22 questionnaire, currently the most widely used tool for assessing health measures across different clinical domains, has been validated among different types of patients with scoliosis ( 24 , 25 ). In this study, we found that patients with CS exhibited significantly lower scores in self-image and mental health domains than those in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gathering patient input in the surgical planning phase is critical to ensuring a favorable postoperative outcome ( 21 - 23 ). The SRS-22 questionnaire, currently the most widely used tool for assessing health measures across different clinical domains, has been validated among different types of patients with scoliosis ( 24 , 25 ). In this study, we found that patients with CS exhibited significantly lower scores in self-image and mental health domains than those in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%